Sistem Informasi Geografis Taman Kanak-Kanak Al-Quran Dan Taman Pendidikan Al-Quran Forum Komunikasi Pendidikan Al-Quran Kabupaten Bintan Berbasis Web - Ade Winarni; Deni Rusandi; Titania Pricillia (Jurnal Bangkit Indonesia, 2020)
Al-Quran education place is known as Al-Quran kindergarten institution or Al-Quran Education Park (TKQ/TPQ), known as 281 TKQ/TPQ institutions in Bintan Regency is spread in 10 jealousy under the coordination of the Quran Education Communication Forum (FKPQ) Bintan Regency is integrated institution that very important and needed by parents who want to give a good Al-Quran education to their children. However, currently there is no application system that presents general information or recommendation to choice of location strategic education where will be visited by the staff of the public or parents in determining the strategic place of education for his daughter's son. Difficulty obtaining information of AL- Quran education place the result in the community lacking a reference of Al-Quran education offered in Bintan Regency. The purpose of this research is to create a Web-based Geographic Information System (GIS) spread of AL-Quran education TKQ/TPQ particular in Bintan Regency using a Web-based mapping approach. Development of GIS TKQ/TPQ Authors use the Waterfall method and the system analysis modelled with UML (Unified Modelling Languange) implemented using PHP programming language and Database MySQLI. The result of this TKQ/TPQ Geographic Information System is expected to help the community to know information about TKQ/TPQ distribution and detail of TKQ/TPQ information to choosing the right place of education, in addition to make easier for FKPQ staff admin to choose the location in official visiting.